Military Budgets, Underdevolpment and Dependency - Nauwelaerts, Philip (Afrika Focus, 1989)
Military expenditures are considered to be one of the causes of underdevelop- ment. This statement is not easy to prove. The article tries to explain that relatively small military expenditures might have large consequences, e.g. on external debt and scarcity of foreign exchange.The problem for Africa is not in the first place the amount of military expenses or external debt,but the low productivity rate which makes repayment difficult. Africa still remains dependent in different economic fields from industrialized countries.The African situation would improve by more stable regimes and a better internal organization of the state, so that natural resources and other activities will really benefit the country. KEYWORDS: military, arms trade, debt, economic dependency